2023
DOI: 10.1111/cns.14283
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary transcriptomic analysis of the orbitofrontal cortex of antisocial individuals

Abstract: AimsAntisocial personality disorder (ASPD) and conduct disorder (CD) are characterized by a persistent pattern of violations of societal norms and others' rights. Ample evidence shows that the pathophysiology of these disorders is contributed by orbitofrontal cortex (OFC) alterations, yet the underlying molecular mechanisms remain elusive. To address this knowledge gap, we performed the first‐ever RNA sequencing study of postmortem OFC samples from subjects with a lifetime diagnosis of ASPD and/or CD.MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Studies on speci c species have demonstrated that different forms and degrees of cognitive impairment are displayed when the mPFC is damaged [26,27]. Among them, the OFC is involved in inhibitory control, and decision-making, emotion and social behavior control [28][29][30][31]. However, fewer studies have been conducted only for REC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on speci c species have demonstrated that different forms and degrees of cognitive impairment are displayed when the mPFC is damaged [26,27]. Among them, the OFC is involved in inhibitory control, and decision-making, emotion and social behavior control [28][29][30][31]. However, fewer studies have been conducted only for REC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the orbitofrontal area plays a role in hedonic experience [14] and reward-driven learning behavior [15] , and direct electrical stimulation to the area has improved mood in patients with epilepsy [16] . Dysfunction of the orbitofrontal are well-established to correlate with antisocial behavior [17] , [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…RNA was sequenced using a NovaSeq Reagent Kit v1.5_150x150 bp (100 M read-pairs) Sequencing (Illumina Inc, San Diego CA, USA) and sequencing libraries were prepared using Illumina TruSeq Stranded Total RNA Library Prep Ribo-Zero Gold kit (Illumina). Transcriptomic analyses on bulk tissues were performed as previously described 52 . For details, see Supplemental Methods.…”
Section: Methodsmentioning
confidence: 99%